Assessing integrated delivery characteristics in hydropower plant projects in Vietnam : a case study of THACMO hydropower station extension project - Che Quang Tan; Hadikusumo, Bonaventura H. W.; Chotchai Charoenngam; Sakul Pochanart; Electricity of Vietnam (EVN) (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Integrated project delivery (IPD) is known as a modern project delivery method that creates high efficiency in the construction industry by providing accurate information and applying new technologies through collaborative environments. The study objective of thesis is TME project that invested by Electricity of Vietnam (EVN) and funded by JICA to supply electricity to the national electricity system of Vietnam with a capacity of 75 MW. The purpose of the thesis is to comprehensively analyze the characteristics of the IPD method and the TME Project through the aspects of contract, process, information & modeling, team and communication. The results show that the TME Project has several strengths and many weaknesses related to IPD characteristics. It is considered the main cause of the delay and cost overruns of the TME Project. Through this study, we also learned lessons learnts and made recommendations for hydropower projects in future.
A project submitted in partial fulfillment of the requirements for the degree of Master of Engineering (Professional) in Construction Engineering and Infrastructure Management
Project (M. Eng.) - Asian Institute of Technology, 2020
Keywords: Project management -- Vietnam; Hydroelectric power plants -- Vietnam